Genetically supported causality between gut microbiota, immune cells, and ischemic stroke: a two-sample Mendelian randomization study - Shuai, Han; Wang, Zi; Xiao, Yinggang; Ge, Yali; Mao, Hua; Gao, Ju (Frontiers in Microbiology, 2024)
Background Previous studies have highlighted a robust correlation between gut microbiota/immune cells and ischemic stroke (IS). However, the precise nature of their causal relationship remains uncertain. To address this gap, our study aims to meticulously investigate the causal association between gut microbiota/immune cells and the likelihood of developing IS, employing a two-sample Mendelian randomization (MR) analysis. Methods Our comprehensive analysis utilized summary statistics from genome-wide association studies (GWAS) on gut microbiota, immune cells, and IS. The primary MR method employed was the inverse variance-weighted (IVW) approach. To address potential pleiotropy and identify outlier genetic variants, we incorporated the Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) technique, along with MR-Egger regression. Heterogeneity was assessed using Cochran’s Q-test. Additionally, leave-one-out analysis was conducted to pinpoint any individual genetic variant influencing the observed causal associations. Finally, a reverse MR analysis was performed to explore the potential of reverse causation. Results Our investigation revealed four gut microbial taxa and 16 immune cells with a significant causal relationship with IS (p < 0.05). Notably, two bacterial features and five immunophenotypes were strongly associated with a lower IS risk: genus.Barnesiella.id.944 (OR: 0.907, 95% CI: 0.836–0.983, p = 0.018), genus.LachnospiraceaeNK4A136group.id.11319 (OR: 0.918, 95% CI: 0.853–0.983, p = 0.988), Activated & resting Treg % CD4++ (OR: 0.977, 95% CI: 0.956–0.998, p = 0.028). Additionally, significant associations between IS risk and two bacterial features along with eleven immunophenotypes were observed: genus.Paraprevotella.id.962 (OR: 1.106, 95% CI: 1.043–1.172, p < 0.001), genus.Streptococcus.id.1853 (OR: 1.119, 95% CI: 1.034–1.210, p = 0.005), CD127 on granulocyte (OR: 1.039, 95% CI: 1.009–1.070, p = 0.011). Our analyses did not reveal heterogeneity based on the Cochrane’s Q-test (p > 0.05) nor indicate instances of horizontal pleiotropy according to MR-Egger and MR-PRESSO analyses (p > 0.05). Furthermore, the robustness of our MR results was confirmed through leave-one-out analysis. Conclusion Our study provides further evidence supporting the potential association between gut microbiota and immune cells in relation to IS, shedding light on the underlying mechanisms that may contribute to this condition. These findings lay a solid foundation for future investigations into targeted prevention strategies.